Yeminli mali müşavirlerin tasdikten doğan sorumlulukları - Akkurt, Mahmut Nedim (My University, 2006)
Bu tezimizle Yeminli Mali Müsavirlerin Tasdikten Dogan Sorumlulukları arastırılmıs, mevcut olan yapının eksik yönleri bulup çıkartılmıs, olması gereken sorumluluklar mevcut düzenlemelerden farklı olarak ortaya konulmustur. Bunları yaparken, önce kavram ele alınmıs, tasdikten dogan kavramın ne oldugu ortaya konmus, sonra terim üzerinde durulmus, tasdikten dogan sorumlulugu karsılayan terimler tespit edilmistir. Yeminli Mali Müsavirlik meslegi bir serbest meslek olduguna göre, diger serbest mesleklerdeki sorumluluklarla benzerlikleri ve farklılıkları irdelenmistir. rdelenen bu meslekler; avukatlık, doktorluk, mimarlık ve müteahhitlik meslekleridir. Daha sonra, Türkiye, ABD ve A.B.’nin önemli ülkelerinden ngiltere, Almanya ve Fransa’da yeminli mali müsavirlerin tarihçeleri incelenmis ve bu incelemeden sonra bu ülkelerdeki mali müsavirlik hukuk düzenine toplu bakılmıs ve hukuk düzenleri irdelenmistir. Tüm bunlar tezin birinci bölümünde yapılmıstır. Tezin kinci Bölümünde; Yeminli Mali Müsavirlerin Tasdikten Dogan Sorumlulugunun Hukuki dayanagı incelenmistir. Serbest Muhasebeci Mali Müsavirlik ve Yeminli Mali Müsavirlik ile ilgili tüm kanunlar, bilhassa 3568 sayılı yasa ve V.U.K. Mük. 227’nci madde ve bu kanunlarla ilgili yönetmelik, tebligler ve yargı kararları incelenmesinde yeminli mali müsavirlerin tasdikten dogan sorumlulukları irdelenmis, kanun, yönetmelik ve tebliglerdeki farklılıklar ortaya konmus, yargı kararlarındaki farklılıklar incelenmistir. Ayrıca bu bölümde Maliye Bakanlıgı’nın meslek yasası üzerindeki çalısması ortaya konmus, TURMOB kurulduktan sonra TURMOB’un çalısmaları incelenmistir. Üçüncü ve son bölümde; Yeminli Mali Müsavirlerin Tasdikten Dogan Sorumlulugunun Yeniden Kurulması; Borçlar Kanunundaki sorumluluk ele alınmıs ve buna, yeminli mali müsavirlerin sorumlulugunun mesleki özen veya mesleki kusurdan dolayı söz konusu olacagı bunun haricindeki bir davranısın adil yargılama ve pozitif hukuka uygun olmayacagı ortaya konmustur.

In this dissertation the responsibilities of certified public accountancy caused by certification are firstly the concept is discussed and the meaning of the concept coming from certification is studied, the deficiencies in current structure are ascertained and the required responsibilities, which are totally different from the current regulations, are put forth for consideration. Firstly the concept is discussed and the meaning of the concept coming from certification is clarified then the term is emphasized and the terms which are meeting the responsibilities created by certification are determined. As the profession of certified public accountancy is a kind of self-employment, the similarities and differences between its responsibilities and the other self-employments’ are examined in details. These examined professions are the professions of a lawyer, a doctor, an architect and a building contractor. In the continuation of the work, short histories of some certified public accountants from Turkey, America, England, Germany and France are investigated. Afterwards the law system of public accountancy is taken as a subject in a general way and then is considered at length. All of these are forming the first part of the dissertation. In the second part of the dissertation the legal basis of certified public accountants’ responsibilities stemming from certification is investigated. All laws about ‘independent accountancy’, and ‘certified public accountancy’ –especially the certified public accountants’ responsibilities, coming from certification, in the investigation of the regulations, notifications and civil jurisdictions about the law numbered as 3568 and the two-hundred twenty-seventh clause of tax procedure law- are explicated, the differences in laws, regulations and notifications are displayed, the differences in civil jurisdictions are analyzed. Furthermore in this part Ministry of Finance’s operation upon the professional law is revealed and TURMOB’s works realized after its establishment are studied. In the and third part, re-construction of certified public accountants’ responsibilities derived from certification and the responsibility in the Code of Obligations are dealt with. Besides it is manifested that the responsibility of certified public accountants will concern with either their professional care or their professional faults; and any behavior excluding this is not going to be proper to the fair judgment and positive law
Keywords: Mali Denetçiler; Mali Hukuk